2019
DOI: 10.1111/vec.12869
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the percutaneous dilatational tracheostomy technique in experimental manikins and canine cadavers

Abstract: Objective: To evaluate procedure time, ease of placement, and complication rates of percutaneous dilatational tracheostomy (PDT) compared to surgical tracheostomy (ST) in canine cadavers. Design: Randomized crossover experimental manikin and cadaver study involving 6 novice veterinary students. Setting: University teaching hospital. Animals: Canine tracheostomy training manikin, 24 canine cadavers. Interventions: None. Measurements and Main Results: For training, each student performed 10 PDT and 10 ST procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…It is possible the authors may have somehow influenced the TT procedure which resulted in longer times. However, a similar study, also using veterinary students as participants (15), found that the standard TT procedure had a median time of 188 s following 10 training attempts on mannikins and one training attempt on a cadaver. The abbreviated TT in this study took a median time of 95.7 s over all attempts, indicating that this was taught in a way to maximise speed.…”
Section: Discussionmentioning
confidence: 93%
“…It is possible the authors may have somehow influenced the TT procedure which resulted in longer times. However, a similar study, also using veterinary students as participants (15), found that the standard TT procedure had a median time of 188 s following 10 training attempts on mannikins and one training attempt on a cadaver. The abbreviated TT in this study took a median time of 95.7 s over all attempts, indicating that this was taught in a way to maximise speed.…”
Section: Discussionmentioning
confidence: 93%
“…Sixty seconds was estimated from the author's experience and similar studies (18)(19)(20). The TT time estimate was based on the study by Pardo et al (15), less the expected time saved with the abbreviated technique. Analyses were conducted in R Statistical program software 3 and Stata version 16.1 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Damage scores were adapted from a similar veterinary study (15). A score was given for each injury ( Table 3).…”
Section: Recordingmentioning
confidence: 99%
“…The students then completed a survey which included a visual analogue scale (VAS), scored from 0 to 10 with 0 being "the easiest procedure you can think of " and 10 being "the most technically challenging procedure you can imagine." This method was adopted from previous similar studies (15,16). Additionally, students were also asked which technique they would select in practice if faced with a CICO event.…”
Section: Recordingmentioning
confidence: 99%
See 1 more Smart Citation